Kebiasaan Makan Ikan Tilan (Mastacembelus erythrotaenia) di Sungai Landak Desa Kuala Mandor A, Kabupaten kbu Raya - Atmaja, Yulius Yudhie Darma; Kurniadi, Bambang (Department of Aquatic Resource Management, Faculty of Agriculture, Universitas Tanjungpura, 2024)
ABSTRACTFish feeding habits are the amount and quality of food that fish eat. Food habits are one aspect that affects the growth and survival of fish. This study aims to understand and study the eating habits of tilan fish in the Landak River Kuala Mandor A, Kubu Raya Regency by analyzing data such as relative intestinal length, stomach fullness index and the composition of food types and determine the condition of the water environment. in the Porcupine river. The research was conducted for 5 months, that is in desember 2022